Quality of family lives: perception of PNCF beneficiaries in Nova Xavantina, Mato Grosso, Brazil - Maia, Ana Heloisa; Sant'Ana, Antonio Lázaro; da Silva, Flaviana Cavalcanti (Guaju: Revista Brasileira de Desenvolvimento Territorial Sustentável, 2022)
This article is the result of a doctoral research that aims to investigate how the family farmers of the Pé da Serra and Beira Rio Settlement, located in the municipality of Nova Xavantina, Mato Grosso, Brazil, see changes / improvements in the quality of life of families, as a result of access to land by PNCF, and the direct repercussions of these on the social and economic reproduction of individuals. The methodology used includes bibliographic review, consultation of data from secondary sources, application of questionnaires to 43 farmers and interviews. The results showed that, in general, there were significant improvements in the quality of life of households after access to land through the PNCF, not only in relation to the acquisition of durable goods, but also in relation to aspects such as housing, purchasing power, leisure, security and future prospects, as well as the feeling of belonging to a place / territory. Other aspects that reflect on the quality of life of families are incipient, especially with regard to collective production infrastructures, forms of social organization (based on the Beira Rio Association) and the interaction of this organization with the settled community, restricted only to initial formation of these settlements.